Analysis Of Benzo(α)pyrene On Chicken Sate With Methods High Performance Liquid Chromatography (Hplc) - Farha, Nazilatul (PROCEEDING SURABAYA INTERNATIONAL HEALTH CONFERENCE 2019, 2020)
Satay is a processed food product from the combustion process. The combustion process can produce carcinogenic compounds. The carcinogenic compound is Polycyclic Aromatic Hydrocarbons (PAH). PAH is a group of compounds that can be formed due to incomplete combustion of the reaction between meat fat dripping over organic and inorganic substances such as charcoal, oil and gas. Benzo(α)pyrene is a member of the five-ringed PAH which is a group of organic compounds that are mutagenic and carcinogenic. the combustion process will produce smoke with high benzo(α)pyrene contaminants. HPLC was chosen to carry out an analysis of benzo(α)pyrene because it has many advantages including the simple and sensitive way it works. This study aims to analyze the levels of benzo(α)pyrene in satay. The type of research used is experimental laboratory, many samples used were 8 samples, namely 1 sample in the form of raw meat as a control material and 7 samples were burned for 5 minutes.